2019
DOI: 10.1177/1535370219826544
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of photodynamic therapy in laryngeal cancer cells – Anin vitrostudy

Abstract: Photodynamic therapy provides the formation of reactive oxygen species that are capable of inducing cell death. Human laryngeal carcinoma (HEp-2) cells have been evaluated in this study under PDT treatment. Cells were treated with photosensitizer aluminum phthalocyanine tetrasulfonate (AlPcS4) and irradiated with a Biopdi/Irrad-Led5 660 LED with 660 nm wavelength, intensity of delivered light of 25 mW/cm2, power of 70 mW, fluence of 5 J/cm2 for 24 h and 48 h, and then evaluated. Cell population was not increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…One of the key causes of cell damage and death in PDT is oxidative DNA damage, which could be induced by free radicals. DNA damage may result in single or double-strand breaks ( 35 , 47 ). When DNA damage occurs, repair mechanisms are activated to sustain the survival and stability of the DNA genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key causes of cell damage and death in PDT is oxidative DNA damage, which could be induced by free radicals. DNA damage may result in single or double-strand breaks ( 35 , 47 ). When DNA damage occurs, repair mechanisms are activated to sustain the survival and stability of the DNA genome.…”
Section: Discussionmentioning
confidence: 99%
“…It functions as an upstream protein that facilitates the phosphorylation of histone H2A variant X (H2A.X) and the activation of p53 for various types of DNA repair responses ( 33 , 34 ). Previous reports have shown that phthalocyanine-based photosensitizers can induce DNA damage and cell death across multiple cancer types ( 35 , 36 ). However, the mechanism by which AlPcS 4 Cl induce DNA damage response and cell death in the oesophageal cancer cell is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability assay evaluates the cytotoxicity of the compound employing a colorimetric test. The method consists of verifying the cell density by staining the DNA, obtaining quantitative information on the relative density of live cells adhered to culture plates, that is, obtaining indirectly the amount of DNA in the samples and consequently the number of cells present in the analyzed groups (Moraes et al, 2019).…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…The whole process was carried out in the dark. Data collected were statistically analyzed (Moraes et al, 2019).…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation